The experience of adolescents being mothers at a young age scoping review - Yunita Anggriani; Nurul Kurniati; Nurul Mahmudah (International Journal of Health Science and Technology, 2021)
Life changes that occur in adolescents who marry at a young age provide challenges for adolescents in living a new life. The period of marriage, pregnancy and childbirth experienced by adolescents at a young age becomes a new transition stage for them to take on a new role to become a mother. The aim of the scoping review is to review evidence related to adolescent experiences of motherhood at a young age. This scoping review used the Arksey and O'Malley framework. Identification of relevant studies used 4 databases. The results of this scoping review consisted of 15 selected articles. The results of the thematic analysis emerged 2 themes, which were the psychological state of adolescents to become mothers at a young age and the support needed by adolescents when they become mothers at a young age.